EFEKTIVITAS PELAKSANAAN E-PROCUREMENT DALAM MENDUKUNG GOOD GOVERNANCE DI PROVINSI RIAU - Suhendri "; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study was based on the phenomenon still often the practice of corruption, collusion and nepotism (KKN) of goods and services by government. So with the e-procurement can be an instrument to prevent and reduce corruption, collusion and nepotism (KKN) because through e-procurement, procurement of goods and services can further enhance transparency and accountability, improve market access and fair competition, improve the level of efficiency of the procurement process, to support the process of monitoring and auditing, and meet the needs of real-time information access. So the purpose of this study was to examine the effectiveness of the implementation of e-procurement in support of good governance in the province of Riau and to determine the factors that influence the effectiveness of the implementation of e-procurement in support of good governance in the province of Riau.Theoretical concepts used are effectiveness, proposed by Mahmudi. This study uses qualitative research methods to study descriptive data. In collecting the data the researcher used interview, observation, and documentation. By using key informants as a source of information and as a source triangulation techniques in testing the validity of the data.Results of this study by using e-procuremen program in the procurement of goods and services within the Riau provincial government has implemented a very effective compared to conventional systems for the perpetrators of the auction services. This is evident from the information regarding the procurement of goods and services can be obtained via internet whenever such information is required, and no need to wait for a later date. The factors that are affecting the success of e-procurement program is a human resources (HR), facilities and infrastructure and sources of funding. Which all of these factors are influential for the achievement of effective implementation of e-procurement in support of good governance in the province of Riau.Keywords : Effectiveness, E-Procurement, Good Governance.